2015
DOI: 10.1590/bjpt-rbf.2014.0100
|View full text |Cite
|
Sign up to set email alerts
|

The role of sensitization in musculoskeletal shoulder pain

Abstract: Introduction: Peripheral and central sensitization are neurophysiological processes that can prolong painful conditions. Painful shoulder conditions are often persistent, perhaps due to the presence of sensitization. Method: This manuscript summarizes six studies that have evaluated those with musculoskeletal shoulder pain for the presence of sensitization. Results: All six manuscripts report evidence of peripheral sensitization, while central sensitization was described in five of the studies. The chronicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 29 publications
(46 reference statements)
1
50
0
Order By: Relevance
“…Additionally, the exclusion criteria did not account for the potential inclusion of individuals with CNS sensitization. Two recent reviews 6,64 suggest that a subgroup of individuals with shoulder pain may exhibit hyperexcitability of the CNS. Gwilym and colleagues 28 reported that a subgroup of individuals with shoulder impingement syndrome and signs of CNS hyperexcitability had significantly worse outcomes postoperatively compared to those without CNS involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the exclusion criteria did not account for the potential inclusion of individuals with CNS sensitization. Two recent reviews 6,64 suggest that a subgroup of individuals with shoulder pain may exhibit hyperexcitability of the CNS. Gwilym and colleagues 28 reported that a subgroup of individuals with shoulder impingement syndrome and signs of CNS hyperexcitability had significantly worse outcomes postoperatively compared to those without CNS involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitisation, a nervous system phenomenon, is in concurrence with pain where normally innocuous input is perceived as painful due to increased nociception (Borstad & Woeste, 2015 ). It is classified into two types - peripheral sensitisation and central sensitisation, which play a significant role in development of musculoskeletal pain (Arendt-Nielsen, Fernández-de-Las-Peña, & Graven-Nielsen, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tmax total delay = Tmax travel + Tmeasure = 24 + 100 = 124 (ms), (Figure 4, c), which is close to the inverse of pain sensitization in its shape [72,73] and demonstrated the best efficiency in most common tasks ( Figure 5). (i) Interact with known objects.…”
Section: Operational Principlesmentioning
confidence: 65%